Design requirement for ice forces - Wong, T. T.; Sego, D. C. (Canadian Geotechnical Journal, 1989)
The procedure of obtaining design ice loads on arctic structures using the American Petroleum Institute (API) Bulletin 2N is first outlined. Then a summary of ice forces measured in the Beaufort Sea and in the laboratory is given, followed by an examination of the physical principles underlying ice–structure interaction. The current trend of advocating a lower design ice pressure is noted and argued against. It is felt that the indentation formula presented in API Bulletin 2N may be capable of providing a simple, reasonable estimate for the design ice pressure provided a modified definition of strain rate is used. Key words: ice pressure, ice forces, indentation, arctic offshore structures.